Enhancing Convolutional Neural Network Robustness Against Image Noise via an Artificial Visual System - Bin Li; Yuki Todo; Sichen Tao; Cheng Tang; Yu Wang (Mathematics)
The convolutional neural network (CNN) was initially inspired by the physiological visual system, and its structure has become increasingly complex after decades of development. Although CNN architectures now have diverged from biological structures, we believe that the mechanism of feature extraction in the visual system can still provide valuable insights for enhancing CNN robustness and stability. In this study, we investigate the mechanism of neuron orientation selectivity and develop an artificial visual system (AVS) referring to the structure of the primary visual system. Through learning on an artificial object orientation dataset, AVS acquires orientation extraction capabilities. Subsequently, we employ the pre-trained AVS as an information pre-processing block at the front of CNNs to regulate their preference for different image features during training. We conducted a comprehensive evaluation of the AVS–CNN framework across different image tasks. Extensive results demonstrated that the CNNs enhanced by AVS exhibit significant model stability enhancement and error rate decrease on noise data. We propose that incorporating biological structures into CNN design still holds great potential for improving overall performance.